Analysis Of Volleyball Extracurricularcity At State Junior High Schools In Bengkulu - Defliyanto Defliyanto; Yarmani Yarmani; Santun Sihombing; Nengsi Kemala Sari (UNIB Press, 2021)
This study aims to determine Analysis of volleyball extracurricular development in junior high schools in Bengkulu city. The type of research used is qualitative with the design of this research is a survey approach. The research subjects, namely coaches, trainers and students at the State Junior High Schools in Bengkulu City which were accredited A totaled 15 schools. The object of this research is volleyball extracurricular at State Junior High Schools in Bengkulu City. The data analysis technique in the field uses the Miles and Huberman model in the form of data reduction, data display, and the last one is drawing conclusions/verification. The results of this study indicate that 15 State Junior High Schools (SMP) in Bengkulu City which consist of 15 coaches, 15 coaches, and 15 students regarding the analysis of volleyball extracurricular coaching at State Junior High Schools in Bengkulu City, it is known that the overall results of the coaching extracurricular activities carried out by the coaches were in the very good category (85.67%) then the trainers were in the good category (76.33%) and the students were in the good category (75.33%). In general, it can be concluded that of the 15 State Junior High Schools in Bengkulu City, it is (79.11%) in the good category..